Self-Reported Diabetes in Older Adults: A Comparison of Prevalence and Related Factors in the Mexican Health and Aging Study (2015, 2018, and 2021) - Alvaro García Pérez; Teresa Villanueva Gutiérrez; Laura Bárbara Velázquez-Olmedo (Journal of Diabetes Research)
Conclusion: An elevated prevalence of diabetes was found in older adults in Mexico, while not having access to social security was associated with a higher possibility of presenting diabetes and living in a rural area was associated with a lower possibility of presenting diabetes. Detection, prevention, and control programs should be implemented to reduce the incidence and severity of the disease in older adults and, thus, prevent its associated complications.